Pembentukan Karakter Religius Anak Usia Dini Melalui Pembiasaan 5S plus Peduli Lingkungan - Zahra, Bulqis Aulia; Khunaifi, Agus (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
The development of religious character through environmental awareness has become an effective new method, making it important to be introduced to children from an early age. This study analyzes the implementation of the 5S habituation (Smile, Greet, Salute, Polite, and Courteous) combined with the reinforcement of environmental awareness at Darul Hasanah Kindergarten, located in Banjardowo Subdistrict, Genuk District, Semarang City. This study uses a descriptive qualitative approach. The data collection techniques used in this study include observation, which was conducted while the children were engaged in activities inside or outside the classroom; interviews, which were carried out with the school principal, teachers, and parents; and documentation, which was used to analyze teaching modules and other documents related to the 5S cultural activities. The results of the study at TK Darul Hasanah show that the habituation of the 5S culture and environmental awareness in shaping children's religious character is consistently implemented through various daily activities at school. This research is expected to broaden the insights of school principals, kindergarten teachers, and parents so that they can help nurture a young generation that is courteous, religious, environmentally conscious, and well prepared to face future challenges with a strong spiritual foundation.